Mathematical models of thrombin generation - Owen, Matt J (2023)
Thrombin generation is a key step in the formation of a blood clot. It is the only enzyme able to cleave the protein fibrinogen into fibrin, which is vital to both the structure and stability of a clot. The formation of thrombin is the result of many positive and negative feedback loops, controlled by a series of proteins called coagulation factors, whose concentrations vary both between individuals and over time. It is the combined effects of all coagulation factors that regulate both the rate and amount of thrombin that is generated.